Translating the effects of statins: From redox regulation to suppression of vascular wall inflammation - Antonopoulos, Alexios S.; Margaritis, Marios; Shirodaria, Cheerag; Antoniades, Charalambos (Thrombosis and Haemostasis, 2012)
Vascular oxidative stress is a key feature of atherogenesis, and targeting vascular redox signalling is a rational therapeutic goal in vascular disease pathogenesis. 3-hydroxy-3-methyl-glutaryl-CoA reductase inhibitors or statins are potent lipid-lowering drugs that improve cardiovascular outcomes. It is now widely accepted that cardiovascular disease prevention by statins is dependent not only on their lipid lowering effects, but also on their beneficial effects on vascular redox signalling. Cell culture and animal models have provided important findings on the effects of statins on vascular redox and nitric oxide bioavailability. Recent evidence from studies on human vessels has further enhanced our understanding of the “pleiotropic” effects of statins on vascular wall. Reversal of endothelial dysfunction in human vessels by statins is dependent on the mevalonate pathway and Rac1 inhibition. These critical steps are responsible for reducing NADPH-oxidase activity and improving tetrahydrobiopterin bioavailability and nitric oxide synthase (NOS) coupling in human vessels. However, mevalonate pathway inhibition has been also held responsible for some of the side effects observed after statin treatment. In this review we summarise the existing knowledge on the effects of statins on vascular biology by discussing key findings from basic science as well as recent evidence from translational studies in humans. Finally, we discuss emerging aspects of statin pleiotropy, such as their effects on adipose tissue biology and adipokine synthesis that may light additional mechanistic links between statin treatment and improvement of clinical outcome in primary and secondary prevention.
Keywords: Statins; NADPH oxidase; eNOS coupling; vascular redox; atherosclerosis